Notions of Mobility in Argentina: a Discussion of the Circulation of Ideas and Their Local Uses and Meanings - Zunino Singh, Dhan Sebastian (2014)
The following critical review of notions of mobility in Argentina is motivated by the rapid spread of this globalized term and how it is being appropriated by transport scholars, policymakers, and technicians. Our concern as sociologists – now involved in cultural history and urban planning – and as members of the Argentinean University Transport Network, is the lack of a profound discussion that allows us to talk about a mobility turn. We argue that the movement from transport to mobility tends to be a semantic change mostly because social sciences and humanities do not lead it, as experienced in other countries. Moreover, we believe that the particular way in which the notions of mobility spread in Argentina must be understood in the context of circulation and reception of ideas, experts, capital and goods, and re-visiting center–periphery debates.